Age and Growth Characteristics of Marbled Electric Ray Torpedo marmorata (Risso, 1810) Inhabiting Iskenderun Bay, North-eastern Mediterranean Sea - Duman, Omer Veli; Basusta, Nuri (Central Fisheries Research Inst, 2013)
The age and growth characteristic of the marbled electric ray (Torpedo marmorata) was determined inhabiting in Iskenderun Bay is located in north-eastern Mediterranean Sea. A total of 117 specimens sampled caught 52% were female and 48% were male. The total length to weight relationship was determined as: W=0.0195xL2.9856. This study is the first known example using known aging methods for this species. The growth parameters that were derived by using the von-Bertalanffy method for this species were: L infinity=57.31cm, k=0.187053 year1 and to=-0.39231 year-1. According to the Marginal Increment Analysis it was found that age band growth was annual. This is the first and only known information in regards to the age and growth of this species.
Kuzeydo?u akdeniz, i?skenderun körfezi'ndeki elektrikli vatoz (Torpedo marmorata)'un yaş ve büyüme özellikleri
Keywords: Marbled electric ray; Torpedinidae; chondrichthyes; staining method; safranin-O